Merlin Volume 1 Episodes 1-3, 4-6, Special Features - Julian Jones; John Hurt; Morgan, Colin; Bradley James; Richard Wilson; Coulby, Angel; Katie McGrath (UK BBC Wales, 2008)
Young Merlin is a teenager, discovering and then learning to master his magical gift. Magister Gaius, King Uther Pendragon's learned court physician to whom he's assigned as humble page, teaches him medicine, coaches his magical self-study, and warns him of Uther's strong aversion to magic. Merlin becomes squire to the noble but imprudent crown prince, Arthur, whose fate is linked with Merlin.
Language: English Subtitle: English
Keywords: Adventure; Drama; Family; Fantasy